Internal auditor’s objectivity threats: an exploratory study in Malaysia - Mohd Razali, Fazlida; Said, Jamaliah; Johari, Razana Juhaida (2016)
Recently, there has been a growing criticism on the internal audit profession for the failure to discharge their responsibility as independent assurers diligently.Amongst the root causes that contribute to the flaws in internal audit judgment is the objectivity issue.The dual roles of an internal auditor (providers of both assurance services within the organization and consultancy services to managers) expose them to the conditions that could threaten their objectivity. The criticality of objectivity concept in the auditing profession is predominantly explored in the context of an external auditor; nevertheless, limited in the context of internal auditor. This paper sought to identify the existence of objectivity threats in the Malaysian internal auditing environment.Data were collected based on the survey of 50 internal auditors working in Malaysian Public and Private Sectors. The survey findings indicated that all nine objectivity threats listed in the “International Standards for Professional Practices of Internal Auditing (IPPF): Practice Guide on Independence and Objectivity” did exist in the Malaysian internal audit environment. The most prevalent objectivity threats included social pressure threat, personal relationship threat and familiarity threat. An internal auditor ranked social pressure threat, economic interest, and personal relationship as the top three threats that could threaten objectivity.The paper provided basic empirical evidence of a potentially serious risk of objectivity threats that may impair the Malaysian internal auditors’ objectivity, thus reducing their ability to make an objective judgment.These empirical evidences are important to create awareness to the individual internal auditors as well as their stakeholders on the condition that could impair the internal auditors’ objectivity. Individual internal auditors need to be able to manage the objectivity threats to provides confidence on their services as independent assurers, whereas stakeholders, especially the Management, could address such threats by implementing preventive measures to ensure that the purpose of having an internal auditor as the second line of defense is fully utilized.